Does Double Jeopardy apply using average spend per buyer as the loyalty metric?. Issue 4 (November 2017) - Dawes, John; Bond, Allison; Hartnett, Nicole; Sharp, Byron
Highlights: Study found that Double Jeopardy applies when average spend per buyer is used as the loyalty metric. Study also found no relationship between excess/deficit loyalty and brand's average selling price. Also no relationship is found between brand size (penetration) and the brand's average selling price. Abstract: Double Jeopardy describes how smaller brands lose twice; they have fewer buyers who are slightly less loyal. A common loyalty measure is how often people buy the brand in a given time period. An alternative loyalty measure is how much people spend, which reflects purchase frequency and price paid. The brand equity literature suggests that high equity brands should reap high purchase rates and high prices. It is therefore possible that Double Jeopardy might become obscured when using a revenue-based measure such as spend per buyer. The reason is that price variation could create more, and more pronounced deviations from the Double Jeopardy pattern. We demonstrate that Double Jeopardy holds for spend in thirteen consumer goods categories: smaller brands have fewer buyers who spend somewhat less on the brand. We further find no relationship between brand share and average price and no relationship between excess/deficit loyalty and average price. Chinese Abstract: 双重危险定律描述了小品牌会遭受双重失败：他们的客户更少，而客户的忠诚度还较低。一个常见的忠诚度衡量值是在特定时期内人们购买品牌的频率。另一个的忠诚度衡量值是人们花费了多少钱，这同时反映了购买频率 和支付 价格。品牌权益类文献表明，高权益品牌应该获得高购买频率和高价格。因此，当使用基于收入的度量（例如每位消费者的花费）时，双重危险定律可能会变得模糊。原因是价格变动可能会产生更多、更明显的与"双重危险"模式的偏差。我们证明双重危险定律对于13种消费品类别的消费度量仍然成立：小品牌，拥有少量的消费者，并且在品牌的花费较少。我们进一步发现品牌份额和平均价格之间没有关系，忠诚度过剩/不足与平均价格之间也没有关系。